Variation in the Phenolic Compounds Profile and Antioxidant Activity in Different Parts of Hawthorn (Crataegus pentagyna Willd.) During Harvest Periods - Jovana Pavlovic; Snežana Mitić; Milan Mitić; Gordana Kocić; Aleksandra Pavlović; Snežana Tošić (Polish Journal of Food and Nutrition Sciences)
Plants of the genus Crataegus , Rosaceae, are widely distributed and have long been used for food and in folk medicine for the treatment of various ailments. This study focused on HPLC-DAD-FLD identification of phenolic compounds of flowers, fruits, and leaves of hawthorn ( Crataegus pentagyna Willd.), on monitoring changes in the content of phenolic compounds during different harvesting periods, as well as on the in vitro testing of the antioxidant activity. Study results showed that neochlorogenic and chlorogenic acids (5.2 and 4.85 mg/g dry weight, respectively) were the most abundant phenolic compounds in the flowers. (-)-Epicatechin and procyanidin B2 were the most abundant phenolic compounds in leaves and fruits. The highest content of phenolic compounds was found in leaves harvested in the early maturity stages, with a tendency of declining in the later stages of maturity. On the other hand, in the case of fruits, the most noticeable changes were found in the content of flavan-3-ols. The highest content of (-)-epicatechin (21.1 mg/g fresh weight) in fruit was in August, and those of procyanidins B2 and B5 in September (10.6 and 3.74 mg/g fresh weight, respectively). Statistical analysis showed a strong correlation between the total phenolics content and the antioxidant activity. This study has demonstrated that there is seasonal variation in both the quantity and the type of phenolic compound as well as the antioxidant activity of different parts of hawthorn.